Development and validation of a rapid visual technique for left ventricular hypertrophy detection from the electrocardiogram - Somani, Sulaiman; Hughes, J. Weston; Ashley, Euan A.; Witteles, Ronald M.; Perez, Marco V. (Frontiers in Cardiovascular Medicine, 2023)
Left ventricular hypertrophy (LVH) detection techniques on by electrocardiogram (ECG) are cumbersome to remember with modest performance. This study validated a rapid technique for LVH detection and measured its performance against other techniques.This was a retrospective cohort study of patients at Stanford Health Care who received ECGs and resting transthoracic echocardiograms (TTE) from 2006 through 2018. The novel technique, Witteles-Somani (WS), assesses for S-and R-wave overlap on adjacent precordial leads. The WS, Sokolow-Lyon, Cornell, and Peguero-Lo Presti techniques were algorithmically implemented on ECGs. Classification metrics, receiver-operator curves, and Pearson correlations measured performance. Age-and sex-adjusted Cox proportional hazard models evaluated associations between incident cardiovascular outcomes and each technique.A total of 53,333 ECG-TTE pairs from 18,873 patients were identified. Of all ECG-TTE pairs, 21,638 (40.6%) had TTE-diagnosed LVH. The WS technique had a sensitivity of 0.46, specificity of 0.66, and AUROC of 0.56, compared to Sokolow-Lyon (AUROC 0.55), Cornell (AUROC 0.63), and Peguero-Lo Presti (AUROC 0.63). Patients meeting LVH by WS technique had a higher risk of cardiovascular mortality (HR 1.18, 95% CI [1.12, 1.24], P < 0.001) and a higher risk of developing any cardiovascular disease (HR 1.29, 95% CI [1.22, 1.36], P < 0.001), myocardial infarction (HR 1.60, 95% CI [1.44, 1.78], P < 0.005), and heart failure (HR 1.24, 95% CI [1.17, 1.32], P < 0.001).The WS criteria is a rapid visual technique for LVH detection with performance like other LVH detection techniques and is associated with incident cardiovascular outcomes.